Technology Entrepreneurship Project (ENT 600) : Decathlon group / Muhammad Zulqarnain Malik - Malik, Muhammad Zulqarnain (2021)
This assignment is about to make a case study about company based on their strength, weakness, opportunity and threat, by knowing their background history, background company, organizational structure, marketing strategies and product and services that’s is provided by the company. The company that I choose is Decathlon group, a famous sport retailer company. There is no doubt that Decathlon is one of the big names when it comes to sports retailer. It is well known for the quality of their product and the affordable price that is shown. I decided to select hiking backpack as the product that I will analyse. After analysing SWOT, I have found some problems about the product. The major problem is the comfortability of the backpack. Some consumer has state that the product is not too comfortable to wear. The best recommendation for the problem is to adjust the strap, the neck and chest area and make it adjustable with more limit. In this study, I will elaborate more details regarding the research objective on the ways to cope with the best solution on solving problems that company faced.